2008
DOI: 10.1038/ni1564
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase Itch regulates expression of transcription factor Foxp3 and airway inflammation by enhancing the function of transcription factor TIEG1

Abstract: Transforming growth factor-β (TGF-β) signaling in naive T cells induces expression of the transcription factor Foxp3, a 'master' regulator of regulatory T cells (T reg cells). However, the molecular mechanisms leading to Foxp3 induction remain unclear. Here we show that Itch −/− T cells were resistant to TGF-β treatment and had less Foxp3 expression. The E3 ubiquitin ligase Itch associated with and promoted conjugation of ubiquitin to the transcription factor TIEG1. Itch cooperated with TIEG1 to induce Foxp3 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
188
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(205 citation statements)
references
References 42 publications
(5 reference statements)
14
188
2
1
Order By: Relevance
“…S7), suggesting that they were induced T regs (iT regs ). Multiple recent reports have elucidated the molecular mechanisms leading to TGF-β-mediated Foxp3 induction in iT regs in a variety of disease settings (41,59,60). By using a Foxp3 reporter, our data support that TGF-β is required for T reg homing to mouse MBs.…”
Section: Discussionsupporting
confidence: 69%
“…S7), suggesting that they were induced T regs (iT regs ). Multiple recent reports have elucidated the molecular mechanisms leading to TGF-β-mediated Foxp3 induction in iT regs in a variety of disease settings (41,59,60). By using a Foxp3 reporter, our data support that TGF-β is required for T reg homing to mouse MBs.…”
Section: Discussionsupporting
confidence: 69%
“…However, a kinetic study of TGF-b1-induced Foxp3 expression showed a time delay between activation of Smad molecules (Smad2 and Smad3) and Foxp3 expression [19], implicating an additional indirect role of Smad on Foxp3 regulation or the importance of a Smad-independent pathway. To support this argument, Venuprasad et al [41] recently reported that TGF-b-inducible early gene-1 product acts as a transcriptional activator for the Foxp3 gene. Though the TGF-b1-induced Smadindependent pathway could be important, we show that its role is not as prominent as the Smad3-and Smad2-dependent direct and indirect pathways.…”
Section: Expression Was Enhanced In T Cells From P50mentioning
confidence: 91%
“…In accordance, Itch À/À Th2 cells are resistant to ionomycin-induced anergy as well as high doses of tolerizing antigen in a mouse model for asthmatic airway inflammation [51]. Moreover, Itch À/À CD4 1 T cells are resistant to T reg -dependent immunosuppression, and Itch À/À T reg cells differentiated in the presence of TGF-b have low expression of Foxp3 and are unable to suppress airway inflammation [52]. In this study, it was proposed that Itch participates in the TGF-b-mediated differentiation of T reg cells by ubiquitiylating and activating the transcription factor TIEG1, which in turn appears to bind to and transactivate the Foxp3 promoter.…”
Section: Itchmentioning
confidence: 86%